Pengaruh Persepsi dan Motivasi Mahasiswa Akuntansi Terhadap Minat Menjadi Akuntan Publik dengan Asas Kemandirian sebagai Variabel Moderasi - Anugrah Nur Wahyuni; Sri Ayem (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2021)
This study aims to determine the effect of perceptions and motivation of accounting students on the interest in becoming a public accountant with the asas kemandirian as a moderating variable. This research was conducted at private universities in DIY which have a CPA test center in collaboration with the Indonesian Institute of Public Accountants (IAPI). The sample was determined using purposive sampling method, so that the total sample was 118 people. The data testing method used is multiple linear regression analysis and moderate regression analysis (MRA). The results of this study indicate that the perceptions and motivation of accounting students have a positive effect on the interest in becoming public accountants. The asas kemandirian strengthens the influence of accounting students' perceptions of their interest in becoming public accountants and has a positive effect. Meanwhile, the asas kemandirian cannot be a moderating variable for the motivation of accounting students to become a public accountant. Keywords: Perception, Motivation, Asas Kemandirian and Interest